New Identity in Local Community-owned Woven Fabrics in Tuban, East Java, Indonesia - Fajar Ciptandi (ITB Journal Publisher, LPPM ITB, 2020)
The tradition of weaving fabrics by the local community in Tuban, East Java, Indonesia began in the 11th century and until now is considered an important part of the identity of the community. In the current conditions, the tradition of making traditional woven fabrics has persisted without improvements in terms of design, technique, function and products. However, the modern context has brought about a new lifestyle in Tuban that is no longer entirely traditional. Therefore, traditional woven fabrics also need a new identity that is compatible with the current conditions while still being connected to the original identity. This was done in the current research by developing visual novelty for the traditional woven fabrics of Tuban using an experimental method. Alternative processes and techniques of weaving were used to produce weavings with a variety of textures. In the development process, keeping elements that are traditionally valued by the local community was a major concern in order to retain the original character of the fabrics while adding novel elements.